Pengaruh Variasi Kecepatan Udara Pada Airfoil NACA 2412 Terhadap Distribusi Tekanan Pada Open Circuit Low Subsonic Wind Tunnel - Kharisma, Aji Abdillah; Agung Ramadhan, Abdul Rahman; Amanda, Bayu (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
An airfoil is a geometric shape that can provide a big lift force and a small resistance force when going through a fluid flow. Airfoil analysis is particularly significant for determining the lift force, drag force, temperature changes, and air pressure distribution that occurs especially in an airplane. In this research, a NACA 2412 series airfoil model was examined using two methods. The initial experiment involved direct study using 3D printing modeling findings, which were evaluated in a wind tunnel. The second test was computerized using Solidworks software. The objective of this study is to compare the results of experiments (experimental) with models of the influence of variations in air speed on the pressure distribution that occurs on the NACA 2412 airfoil. The results of the analysis of wind tunnel tests are changes in the maximum air pressure distribution that occurs, specifically at a speed variation of 5 m /s = 101344.62 Pa, 10 m/s = 101418.195 Pa, 15 m/s = 101560.44 Pa, and 20 m/s = 101737.02 Pa. According to the findings of this study, the higher the wind or air speed, the greater the pressure distribution.